2013
DOI: 10.1037/a0029989
|View full text |Cite
|
Sign up to set email alerts
|

Implicit misattribution of evaluative responses: Contingency-unaware evaluative conditioning requires simultaneous stimulus presentations.

Abstract: Recent research has shown that evaluative conditioning (EC) procedures can change attitudes without participants' awareness of the contingencies between conditioned and unconditioned stimuli (Hütter, Sweldens, Stahl, Unkelbach, & Klauer, 2012). We present a theoretical explanation and boundary condition for the emergence of unaware EC effects based on the implicit misattribution of evaluative responses from unconditioned to conditioned stimuli. We hypothesize that such misattribution is only possible when cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(97 citation statements)
references
References 30 publications
2
92
0
Order By: Relevance
“…I believe implicit misattribution is one possible way in which S -R associations could be created, and for it to occur, simultaneous presentations are likely crucial. As corroborating evidence, there are now several studies which have demonstrated with different methodologies the superiority of simultaneous CS -US presentations in generating EC effects in the absence of contingency awareness (Hütter & Sweldens, 2013;Stahl & Heycke, 2016). Yet, I also believe S -R representations can be formed by psychological processes that are very different from implicit misattribution.…”
Section: How To Create S -S Versus S -R Associationsmentioning
confidence: 78%
“…I believe implicit misattribution is one possible way in which S -R associations could be created, and for it to occur, simultaneous presentations are likely crucial. As corroborating evidence, there are now several studies which have demonstrated with different methodologies the superiority of simultaneous CS -US presentations in generating EC effects in the absence of contingency awareness (Hütter & Sweldens, 2013;Stahl & Heycke, 2016). Yet, I also believe S -R representations can be formed by psychological processes that are very different from implicit misattribution.…”
Section: How To Create S -S Versus S -R Associationsmentioning
confidence: 78%
“…However, several researchers have suggested that implicit processes more likely affect implicit than explicit attitudes (Gawronski & Bodenhausen, 2006). As implicit misattribution is an automatic and implicit process (Hütter & Sweldens, 2012), its impact on implicit attitudes could be stronger than its impact on explicit attitudes. Moreover, Wennekers, Vandeberg, Zoon, and van Reijmersdal (2015) suggested that subtle placements more likely cause an implicit affect transfer and influence implicit brand attitudes, whereas prominent placements tend to cause a more cognitive form of affect transfer and therefore influence explicit brand attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous research has shown that repeated pairings with various different (not identical) negative or positive stimuli can also affect the viewer's attitude toward the brand (Stahl & Unkelbach, 2009;Sweldens et al, 2010). The affective reaction caused by the different affective stimuli may be implicitly misattributed to the brand when presented simultaneously (Jones, Fazio, & Olson, 2009;Hütter & Sweldens, 2012). This effect is referred to as direct evaluative conditioning, because the affect becomes directly associated with the neutral stimulus (stimulus-response association; Sweldens et al, 2010).…”
mentioning
confidence: 99%
“…Thus, when clearly negative text is superimposed across an image, the affect which is automatically experienced when briefly scanning the text can be misattributed to the individual saliently depicted in the picture (Hütter & Sweldens, 2013;Jones, Fazio, & Olson, 2009). Such a style of web-browsing may discourage those interested in the more thoughtful and energy-consuming modes of social influence, but it is well-suited for the sorts of influences argued to be so pervasive by implicit attitudes researchers.…”
Section: Source Confusability + Affective Misattribution = the Internet?mentioning
confidence: 99%
“…Our work and others (Hütter & Sweldens, 2013;Jones, Fazio, & Olson, 2009) has shown that elements presented simultaneously or in close proximity can generate "source confusability" regarding the affect generated by the perceptual experience such that affect from one object is misattributed to the other. Affect is more likely to be misattributed when elements are presented in close proximity and when eye-gaze shifts between them are facilitated (Jones et al, 2009).…”
Section: Context Effects On Evaluative Associationmentioning
confidence: 99%